Eating disorders - knowledge, attitudes, management and clinical experience of Norwegian dentists. Issue 1 (December 2015) - Johansson, Ann-Katrin; Johansson, Anders; Nohlert, Eva; Norring, Claes; Åstrøm, Anne; Tegelberg, Åke
Abstract Background The purpose of this study was to investigate knowledge, attitudes and clinical experience with regard to patients with eating disorders (ED) among Norwegian dentists. Methods In 2010, a questionnaire was sent to all dentists in Norway (N  = 4282) comprising 33 questions related to demographics of the participating dentists, their knowledge of ED (general and oral health aspects), clinical experience, attitudes and perceived management preferences. Results The participation rate was 40 % (47 % women and 53 % men). Their knowledge about ED was often retrieved from common media sources and the greater part of the participants reported they had seen very few patients with ED during their professional career. Female dentists reported superior knowledge about ED compared to males, but the former experienced greater difficulties to inform about the condition. Referrals of the patient to other health facilities were significantly more common among female compared to male dentists. The majority of dentists (76 %) reported a need of more education related to ED management. Conclusions The Norwegian dentists in this study reported limited clinical experience and insufficient knowledge regarding ED. There is therefore a need to increase both undergraduate and continuing education in this field, which can improve preventive and management measures that a dentist can provide for ED patients.